VD_FINDINFO HC / 2017 / 459 vom 13. Juli 2017 - VD Tribunal cantonal (2017)
DESSOUS-DE-TABLE, STIPULATION POUR AUTRUI, VENTE, CONTRAT DE DÉPÔT, NOTAIRE, ESCROW AGENT | 112 CO, 472 al. 1 CO, 44 al. 4 LNo